Tendon blood flow, angiogenesis, and tendinopathy pathogenesis. Issue 6 (27th September 2021) - Merkel, Max Flemming Ravn; Hellsten, Ylva; Magnusson, Stig Peter; Kjaer, Michael
Abstract : Physical exercise results in a duration and intensity‐dependent vascular response in healthy human tendon. In overused (tendinopathy) and damaged tendon, angiogenic pathways are activated and neovascularization is observed. Whereas no direct relationship exists between the amount of neovessels and degree of tendinopathy symptoms, almost all tendinopathic patients have elevated neovascularization and tendon blood flow, as assessed by Doppler ultrasound methodology. The enhanced flow in tendinopathy can be successfully abolished by heavy resistance training. Already in the early time‐phase of tendinopathy (<3 months), neovascularization in the tendon exists but the causal sequence of vascular, metabolic, nociceptive, and matrix tissue changes in tendon pathology is not fully understood. Nevertheless, existing evidences point at neovascularization being an important component of pathogenesis and may occur already before the development of clinical symptoms in tendinopathy.